Khilafah Political Controversy in Indonesia - Indra Utama Tanjung (Universitas Syiah Kuala, 2023)
This paper aims to investigate the political controversy surrounding the caliphate in Indonesia. Using a qualitative approach, this study explores the perspectives of various stakeholders on the topic, including religious leaders, politicians and the general public. The study also analyzes the historical background and current political environment in Indonesia to understand the context of the controversy, using normative juridical research methods. Indonesia is the world's most populous Muslim country, and the idea of a caliphate has been the subject of political controversy for many years. A caliphate is an Islamic state led by a supreme religious and political leader, known as the caliph, who is considered the successor of the Prophet Muhammad. The concept of the caliphate has been a subject of debate among scholars and political leaders in Indonesia, with some in favor and others opposed. The results show that the controversy surrounding the caliphate in Indonesia is complex and multi-dimensional, with a variety of opinions and perspectives. Some argue that the caliphate is essential for uniting the Muslim world and reviving the prestige of Islam, while others believe that the caliphate is incompatible with the principles of democracy and the diversity of the Indonesian population. The research also emphasizes the role of politics in shaping the debate and the impact of external factors, such as global politics and the actions of Islamic extremist groups. This research contributes to a better understanding of the political controversy surrounding the caliphate in Indonesia and its potential impact on Indonesia's future. The findings can inform policy decisions and provide insights for future research on related subjects.